2019
DOI: 10.33019/aquatropica.v4i2.2222
|View full text |Cite
|
Sign up to set email alerts
|

BLOOD PREVIEW OF TILAPIA (Oreochromis niloticus) GIVEN FORTIFIED FEED OF SALAM LEAF (Syzygium polyanthum) LIQUID EXTRACT

Abstract: Tilapia (Oreochromis niloticus) is populer as resistant fish to environmental changes. Cultivating fish with a high stocking density can cause a decrease in water quality. It has an impact on susceptibility to disease due to decreased water quality. Immunostimulants from Phyto-pharmacy are needed to improve the non-specific immune system of fish from natural ingredients. Bay leaves (Syzigium polyanthum) have the potential to be used as an immunostimulant in fish. This study aimed to evaluate the extract of Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…The hematological parameters analyzed were erythrocytes, leukocytes, hemoglobin, hematocrit and micronuclei. Observation of erythrocytes and leukocytes using a haemocytometer (Putranto et al, 2019), hemoglobin was observed using the Sahli method, hematocrit was observed using microhematocrit and micronuclei using the smear method and calculations using a microscope at 1000x magnification (Naqvi et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The hematological parameters analyzed were erythrocytes, leukocytes, hemoglobin, hematocrit and micronuclei. Observation of erythrocytes and leukocytes using a haemocytometer (Putranto et al, 2019), hemoglobin was observed using the Sahli method, hematocrit was observed using microhematocrit and micronuclei using the smear method and calculations using a microscope at 1000x magnification (Naqvi et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The variation in hematocrit levels in the fish's body is determined by the size and quantity of erythrocytes present. Pathogenic germs can also contribute to a drop in the hematocrit number [33].…”
Section: Profile Of Blood Tawes Fish (Barbonymus Gononiotus)mentioning
confidence: 99%
“…Hematokrit adalah presentase volume di dalam darah, sedangkan menurut Putranto et al (2019), Hematokrit yaitu suatu persentase dari volume sel darah merah yang terdapat pada tubuh ikan. Kadar hematokrit terdapat pada Gambar 5, tertinggi pada perlakuan E diperoleh nilai 25,62% sedangkan paling rendah pada perlakuan B sebanyak 8,7%.…”
Section: Pembahasanunclassified
“…Peningkatan hemoglobin dipengaruhi oleh meningkatnya jumlah eritrosit di dalam tubuh ikan (Putranto et al, 2019). Diduga kadar hemoglobin ikan nila apabila diberi pakan tambahan probiotik yang di campurkan ke dalam pakan lebih optimal serta dikatakan normal dibandingkan hanya memberikan probiotik pada media air.…”
Section: Pembahasanunclassified